Multi-colony tracking of a marine central place forager reveals a site specific yet broadly consistent foraging strategy - Jonathan M. Handley; Joshua C. Wilson; Norman Ratcliffe; Alastair M. M. Baylis; Sarah Crofts; Pierre A. Pistorius (Marine Biology, 2026)
Colonial central place foraging seabirds with a wide species range inhabit highly heterogenous habitats, which may result in colony-specific foraging behaviours. Simultaneously tracking seabirds from multiple colonies is key to elucidating factors influencing foraging behaviour and determining how species might respond to environmental perturbations. Here, we investigate the foraging behaviour of gentoo penguins ( Pygoscelis papua ) breeding at the Falkland Islands in relation to habitat availability and prey types. We examine the horizontal and vertical foraging distribution of 78 birds during two breeding seasons from three colonies, selected for their geographic separation and contrasting habitats. Through comparison of general foraging characteristics, we found that at each colony, penguins exhibited either pelagic foraging behaviour in the water column, or benthic foraging behaviour near to the sea floor. This was dictated by the surrounding bathymetry, with pelagic behaviour being associated with steeper surrounding slopes, and was in accordance with the known diet of birds. Then, using a hurdle model to predict dive intensity around each colony, we show that habitat suitability for all colonies declined once distance to the colony exceeded ~ 30 km, while other variables had differing influences. At different colonies, the use of either pelagic or benthic foraging behaviours suggests that gentoo penguins have the capacity to respond to variable environmental conditions. However, given that foraging trips only reached mean maximum distances of 23.1 km ± 12.2 km from the colony during the breeding season, marine spatial planning efforts need to protect inshore waters around critical gentoo penguin colonies to effectively conserve the species.

Intraoperative drug delivery to hindbrain tumours via an injectable hydrogel is well tolerated and confers survival benefit against atypical teratoid/rhabdoid xenografts - Cara Moloney; Phoebe McCrorie; Amr ElSherbeny; Harry Porter; Chiara Bastiancich; Hasan Slika; Aanya Shahani; Emre Derin; Esteban Velarde; Jackson Miller; John Theodore; Khushi Varshney; et al. (Drug Delivery and Translational Research, 2026)

The global proliferation of aquatic, benthic Microcoleus: Taxonomy, distribution, toxin production, ecology, and future directions - Laura T. Kelly; Daniel G. Beach; Joanna R. Blaszczak; Keith Bouma-Gregson; Sydney M. Brown; Haowu Cheng; Janette L. Davidson; Jutta Fastner; Marcus Francis; Andrea Garcia Jimenez; Laurel Genzoli; Ramesh Goel; et al. (Water Research, 2026)

Intentional take of seabirds for human consumption: a global review to inform conservation and policy needs for migratory species - Jonathan M. Handley; Joanne Morten; G. Barry Baker; Aline Küehl-Stenzel; Maximin K. Djondo; Graeme A. Taylor; Iván Ramirez; Heidrun Frisch-Nwakanma; Noëlle F. Kümpel; Tammy E. Davies (Biological Conservation, 2026)

A 2026 horizon scan for biodiversity conservation in South Africa - Colleen L. Seymour; Krystal A. Tolley; Tsungai Zengeya; Dian Spear; Jeran A. Cloete; Anisha Dayaram; Jessica M. da Silva; Graham J. Alexander; Kate Handley; Grant S. Joseph; Lavhelesani D. Simba; Kate Snaddon; et al. (Ambio, 2026)
Horizon scans identify potential changes, enabling proactive rather than reactive conservation strategies. Here, in a follow up to the 2020 horizon scan, 14 biodiversity professionals from different sectors identify ten emerging issues potentially relevant to biodiversity conservation in South Africa over the next 5–10 years. The issues identified highlight three critical needs: adaptive governance systems, cross-sectoral collaboration capacity, and vigilance around new technologies that may simultaneously offer solutions and create new environmental pressures. We plotted these issues along axes of social agreement and scientific certainty, to ascertain whether issues might be "simple" (amenable to solutions from science alone), "complicated" (socially agreed upon but technically complicated), "complex" (scientifically challenging and condisderable levels of social disagreement) or "chaotic" (high social disagreement and highly scientifically challenging). Only one issue was likely to be addressed with improved science alone, but the remainder were all “complex”, requiring social, economic and political engagement.

Pan‐Arctic Peatlands Have Expanded During Recent Warming - J. Handley; R. E. Fewster; T. G. Sim; S. Hodson; B. Parker; K. Crichton; D. Charman; K. Anderson; M. Garneau; M. Väliranta; D. W. Beilman; G. T. Swindles; et al. (Global Change Biology, 2026)
The fate of carbon stored in Arctic peatlands remains uncertain because of the complex nature of the effects of climate change on permafrost and peatland carbon cycling. Expansion and/or shrinkage of Arctic peatlands under climate change also remain unknown due to lack of ground data and difficulties detecting changes in the extent of these ecosystems, meaning that land surface model predictions currently inadequately quantify Arctic terrestrial carbon storage changes. Pan‐Arctic shifts in peatland extent would profoundly change the fate of carbon in the terrestrial Arctic. Here, we tackle this knowledge gap by answering three main questions: (a) has lateral expansion occurred in Arctic peatlands as a response to recent warming? (b) if so, how fast has this occurred? (c) how does the response vary regionally? To answer these, we collected a dataset (12 peatland sites, 91 peat cores) combining peat cores collected across two latitudinal (north–south) transects: one in the European Arctic and one in the Canadian Arctic. In each region, we selected three peatland sites, with cores collected from transects spanning the peat‐edge to the peat‐centre. Our large‐scale dataset shows that peatlands have expanded, often rapidly, with some rates exceeding ~1 m per year since 1950 AD. This rapid expansion has occurred during a period of widespread Arctic warming and is still ongoing: two thirds (8/12) of our peatland sites evidence new peat formation after ~1990 AD based on age‐depth models constrained by 14 C and 210 Pb dating. Given that our sites comprise a broad range of Arctic conditions, we expect peatland expansion to be a pan‐Arctic phenomenon. Within specific regions, there are constraints on peat expansion including topographical limits, but we present the basis for future work to estimate pan‐Arctic peatland expansion, plus the associated carbon cycle implications under future climate change.

Decision-making and ecosystem service dimensions of managed dyke realignment in the complex coastal landscapes of the Bay of Fundy - Lara Cornejo; Elson Ian Nyl Ebreo Galang; Kate Sherren; Jeremy Lundholm; Danika van Proosdij; Will Balser; Elena Bennett; Tony M. Bowron; Kirsten Ellis; Jonathan Fowler; Jennifer Graham; Patrick James; et al. (Ocean & Coastal Management, 2025)

Environmental surveillance for Salmonella Typhi to detect the typhoid burden in Yogyakarta, Indonesia - Vicka Oktaria; Indah Kartika Murni; Amanda Handley; Celeste M. Donato; Titik Nuryastuti; Endah Supriyati; David T. McCarthy; Emma Watts; Rizka Dinari; Hendri Marinda Sari; Jarir At Thobari; Ida Safitri Laksono; et al. (International Journal of Hygiene and Environmental Health, 2025)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Scaling up ocean conservation through recognition of key biodiversity areas in the Southern Ocean from multispecies tracking data - Sarah L. Becker; Charlotte Boyd; Jonathan M. Handley; Ben Raymond; Ryan Reisinger; Yan Ropert‐Coudert; Nora Apelgren; Tammy E. Davies; Mary‐Anne Lea; Mercedes Santos; Philip N. Trathan; Anton P. Van de Putte; et al. (Conservation Biology, 2025)
Biodiversity is critical for maintaining ecosystem function but is threatened by increasing anthropogenic pressures. In the Southern Ocean, a highly biologically productive region containing many endemic species, proactive management is urgently needed to mitigate increasing pressures from fishing, climate change, and tourism. Site‐based conservation is one important tool for managing the negative impacts of human activities on ecosystems. The Key Biodiversity Area (KBA) Standard is a standardized framework used to define sites vital for the persistence of global biodiversity based on criteria and quantitative thresholds. We used tracking data from 14 species of Antarctic and subantarctic seabirds and pinnipeds from the publicly available Retrospective Analysis of Antarctic Tracking Data (RAATD) data set to define KBAs for a diverse suite of marine predators. We used track2kba, an R package that supports identification of KBAs from telemetry data through identification of highly used habitat areas and estimates of local abundance within sites. We compared abundance estimates at each site with thresholds for KBA criteria A1, B1, and D1 (related to globally threatened species, individual geographically restricted species, and demographic aggregations, respectively). We identified 30 potential KBAs for 13 species distributed throughout the Southern Ocean that were vital for each individual species, population, and life‐history stage for which they were determined. These areas were identified as highly used by these populations based on observational data and complement the ongoing habitat modeling and bioregionalization work that has been used to prioritize conservation areas in this region. Although further work is needed to identify potential KBAs based on additional current and future data sets, we highlight the benefits of utilizing KBAs as part of a holistic approach to marine conservation, given their significant value as a global conservation tool.

The BirdLife Seabird Tracking Database: 20 years of collaboration for marine conservation - Ana P.B. Carneiro; Maria P. Dias; Bethany L. Clark; Elizabeth J. Pearmain; Jonathan Handley; Amy R. Hodgson; John P. Croxall; Richard A. Phillips; Steffen Oppel; Joanne M. Morten; Ben Lascelles; Cleo Cunningham; et al. (Biological Conservation, 2024)

Single cell, Label free Characterisation of Human Mesenchymal Stromal cell Stemness and Future Growth Potential by Autofluorescence Multispectral Imaging - Jared M. Campbell; Abbas Habibalahi; Adnan Agha; Shannon Handley; Aline Knab; Xiaohu Xu; Akanksha Bhargava; Zhilin Lei; Max Mackevicius; Yuan Tian; Saabah B. Mahbub; Ayad G. Anwer; et al. (Stem Cell Reviews and Reports, 2024)
Aim To use autofluorescence multispectral imaging (AFMI) to develop a non-invasive assay for the in-depth characterisation of human bone marrow derived mesenchymal stromal cells (hBM-MSCs). Methods hBM-MSCs were imaged by AFMI on gridded dishes, stained for endpoints of interest (STRO-1 positivity, alkaline phosphatase, beta galactosidase, DNA content) then relocated and results correlated. Intensity, texture and morphological features were used to characterise the colour distribution of regions of interest, and canonical discriminant analysis was used to separate groups. Additionally, hBM-MSC lines were cultured to arrest, with AFMI images taken after each passage to investigate whether an assay could be developed for growth potential. Results STRO-1 positivity could be predicted with a receiver operator characteristic area under the curve (AUC) of 0.67. For spontaneous differentiation this was 0.66, for entry to the cell-cycle it was 0.77 and for senescence it was 0.77. Growth potential (population doublings remaining) was estimated with an RMSPE = 2.296. The Mean Absolute Error of the final prediction model indicated that growth potential could be predicted with an error of ± 1.86 doublings remaining. Conclusions This non-invasive methodology enabled the in-depth characterisation of hBM-MSCs from a single assay. This approach is advantageous for clinical applications as well as research and stands out for the characterisation of both present status as well as future behaviour. The use of data from five MSC lines with heterogenous AFMI profiles supports potential generalisability. Graphical Abstract

Pre-Hispanic terrace agricultural practices and long-distance transfer of plant taxa in the southern-central Peruvian Andes revealed by phytolith and pollen analysis - Josephine Handley; Nicholas Branch; Frank M. Meddens; Michael Simmonds; José Iriarte (Vegetation History and Archaeobotany, 2024)
The archaeological excavation of two abandoned prehispanic agricultural terraces (Infiernillo and Tocotoccasa) in the Chicha-Soras Valley (Apurimac) in southern-central Peru revealed the presence of palaeosols. The palaeosols represent soil that developed following construction of agricultural terraces during the Middle Horizon. The soil profiles at the current surface developed following reconstruction of the terraces during the Late Intermediate Period. Phytolith analysis revealed an unexpected presence of Arecaceae (palm family) and Marantaceae (arrowroot family) in both terraces, which has been attributed to local cultivation and/or transportation and use of soil, dung, plant material or implements (made of Arecaceae) on the terrace surfaces. Pollen analysis of a nearby wetland (Ayapampa) did not provide evidence for Arecaceae or Marantaceae. Both phytolith and pollen analysis of the terraces and wetland (respectively) indicated that Zea mays was cultivated locally during the Middle Horizon and Late Intermediate Period, although phytoliths of maize are absent from the wetland record during the Middle Horizon. The presence of Solanaceae and Chenopodiaceae/Amaranthaceae pollen in the wetland may be indicative of cultivation of further important taxa during the Middle Horizon and Late Intermediate Period, which continued into the Late Horizon together with Zea mays .

Sources of variation in community composition of the hindgut microbiota in two tropical Kyphosus species - Alessandro Pisaniello; Lilly D. Bojarski; Kim M. Handley; W. Lindsey White; Esther R. Angert; Kendall D. Clements (Coral Reefs, 2022)
Gut microbiota play a fundamental role in the nutrition of many vertebrate herbivores through foregut and hindgut fermentation of plant carbohydrates. Some species of marine herbivorous fishes contain moderate to high levels of short-chain fatty acids in the hindgut, indicating the importance of hindgut fermentation. Herbivorous fish hindgut microbiota are diverse and can vary with geographic location, but data on the scale of geographic variation involving a few km of separation are limited. Here, we used the 16S rRNA gene to describe community composition of the gut microbiota of the herbivorous species Kyphosus vaigiensis and K. cinerascens collected in the vicinity of Lizard Island, northern Great Barrier Reef, Australia, in 2011 and 2017. Microbiota community structure differed between posterior hindgut sections, host species, sampling years and two mid-shelf and outer reef locations approximately 20 km apart. Hindgut bacterial community composition varied remarkably between mid-shelf and outer reef locations, and among individual fish on the mid-shelf reef. In both fish species, the most abundant phyla were Pseudomonadota, Bacillota and Bacteroidota, followed by Spirochaetota, Thermodesulfobacteriota and Verrucomicrobiota. There were no clear differences between the host species in terms of the relative abundance and composition of bacterial genera in outer reef samples. In contrast, the dominant genera differed between mid-shelf samples of K. cinerascens and K. vaigiensis , being Endozoicomonas- like (Pseudomonadota) and Brevinema (Spirochaetota), respectively. Endozoicomonas are emerging as important symbionts in many marine hosts worldwide and are thought to be important in the coral sulphur cycle. Differences in microbiota composition were not associated with variation in fish condition, suggesting that the different microbial taxa perform equivalent functional roles.

Estrogen Enhances Dendrite Spine Function and Recovers Deficits in Neuroplasticity in the prpTDP-43A315T Mouse Model of Amyotrophic Lateral Sclerosis - Emily E. Handley; Laura A. Reale; Jyoti A. Chuckowree; Marcus S. Dyer; Grace L. Barnett; Courtney M. Clark; William Bennett; Tracey C. Dickson; Catherine A. Blizzard (Molecular Neurobiology, 2022)
Amyotrophic lateral sclerosis (ALS) attacks the corticomotor system, with motor cortex function affected early in disease. Younger females have a lower relative risk of succumbing to ALS than males and older females, implicating a role for female sex hormones in disease progression. However, the mechanisms driving this dimorphic incidence are still largely unknown. We endeavoured to determine if estrogen mitigates disease progression and pathogenesis, focussing upon the dendritic spine as a site of action. Using two-photon live imaging we identify, in the prp TDP-43 A315T mouse model of ALS, that dendritic spines in the male motor cortex have a reduced capacity for remodelling than their wild-type controls. In contrast, females show higher capacity for remodelling, with peak plasticity corresponding to highest estrogen levels during the estrous cycle. Estrogen manipulation through ovariectomies and estrogen replacement with 17β estradiol in vivo was found to significantly alter spine density and mitigate disease severity. Collectively, these findings reveal that synpatic plasticity is reduced in ALS, which can be amelioriated with estrogen, in conjuction with improved disease outcomes.

Estuarine microbial diversity and nitrogen cycling increase along sand–mud gradients independent of salinity and distance - Jian Sheng Boey; Redmond Mortimer; Agathe Couturier; Katie Worrallo; Kim M. Handley (Environmental Microbiology, 2022)
Summary Estuaries are depositional environments prone to terrigenous mud sedimentation. While macrofaunal diversity and nitrogen retention are greatly affected by changes in sedimentary mud content, its impact on prokaryotic diversity and nitrogen cycling activity remains understudied. We characterized the composition of estuarine tidal flat prokaryotic communities spanning a habitat range from sandy to muddy sediments, while controlling for salinity and distance. We also determined the diversity, abundance and expression of ammonia oxidizers and N 2 O‐reducers within these communities by amoA and clade I nosZ gene and transcript analysis. Results show that prokaryotic communities and nitrogen cycling fractions were sensitive to changes in sedimentary mud content, and that changes in the overall community were driven by a small number of phyla. Significant changes occurred in prokaryotic communities and N 2 O‐reducing fractions with only a 3% increase in mud, while thresholds for ammonia oxidizers were less distinct, suggesting other factors are also important for structuring these guilds. Expression of nitrogen cycling genes was substantially higher in muddier sediments, and results indicate that the potential for coupled nitrification–denitrification became increasingly prevalent as mud content increased. Altogether, results demonstrate that mud content is a strong environmental driver of diversity and N‐cycling dynamics in estuarine microbial communities.

Marine Important Bird and Biodiversity Areas for Penguins in Antarctica, Targets for Conservation Action - Jonathan Handley; Marie-Morgane Rouyer; Elizabeth J. Pearmain; Victoria Warwick-Evans; Katharina Teschke; Jefferson T. Hinke; Heather Lynch; Louise Emmerson; Colin Southwell; Gary Griffith; César A. Cárdenas; Aldina M. A. Franco; et al. (Frontiers in Marine Science, 2021)
Global targets for area-based conservation and management must move beyond threshold-based targets alone and must account for the quality of such areas. In the Southern Ocean around Antarctica, a region where key biodiversity faces unprecedented risks from climate change and where there is a growing demand to extract resources, a number of marine areas have been afforded enhanced conservation or management measures through two adopted marine protected areas (MPAs). However, evidence suggests that additional high quality areas could benefit from a proposed network of MPAs. Penguins offer a particular opportunity to identify high quality areas because these birds, as highly visible central-place foragers, are considered indicator species whose populations reflect the state of the surrounding marine environment. We compiled a comprehensive dataset of the location of penguin colonies and their associated abundance estimates in Antarctica. We then estimated the at-sea distribution of birds based on information derived from tracking data and through the application of a modified foraging radius approach with a density decay function to identify some of the most important marine areas for chick-rearing adult penguins throughout waters surrounding Antarctica following the Important Bird and Biodiversity Area (IBA) framework. Additionally, we assessed how marine IBAs overlapped with the currently adopted and proposed network of key management areas (primarily MPAs), and how the krill fishery likely overlapped with marine IBAs over the past five decades. We identified 63 marine IBAs throughout Antarctic waters and found that were the proposed MPAs to be adopted, the permanent conservation of high quality areas for penguin species would increase by between 49 and 100% depending on the species. Furthermore, our data show that, despite a generally contracting range of operation by the krill fishery in Antarctica over the past five decades, a consistently disproportionate amount of krill is being harvested within marine IBAs compared to the total area in which the fishery operates. Our results support the designation of the proposed MPA network and offer additional guidance as to where decision-makers should act before further perturbation occurs in the Antarctic marine ecosystem.

Engineered biosynthesis of cyclotides - Thomas N. G. Handley; Hyon-Xhi Tan; Malcolm T. Rutledge; Hans Henning Brewitz; Joel D. A. Tyndall; Torsten Kleffmann; Margi I. Butler; Russell T. M. Poulter; Sigurd M. Wilbanks (New Zealand Journal of Botany, 2020)

Serum antibodies against Toxoplasma gondii and Neospora caninum in southeast Queensland dugongs - Arthur Wong; Janet M. Lanyon; Ryan O'Handley; Richard Linedale; Lucy Woolford; Trevor Long; Graham R. Leggatt (Marine Mammal Science, 2020)
The dugong ( Dugong dugon ) is an herbivorous marine mammal that inhabits tropical inshore waters and thus may be vulnerable to pollutants and terrestrial pathogens as a result of coastal runoff. In this study, serum samples collected from live, wild dugongs ( n = 114) in an embayment located on the urbanized southeast Queensland coast of Australia during 2008–2014, were measured for IgG antibody levels specific to Toxoplasma gondii and Neospora caninum . An ELISA used to measure T. gondii tachyzoite antibodies indicated a non‐Gaussian distribution of antibody level, with five dugongs identified as high outliers. Mean levels of antibodies specific for T. gondii in dugongs sampled in 2014 were significantly higher than in 2010 ( p = .006) and 2011 ( p = .009) with an elevation in mean antibody levels after a major 2011 flood event relative to antibody levels prior to the flood ( p N. caninum antibody indicated a normal distribution of antibody with no high outliers. Mean antibody level for N. caninum was highest in 2012 and declined significantly in 2014 ( p = .004). This is the first survey of antibodies directed against T. gondii and N. caninum in dugongs and suggests future health monitoring of this species.

Following Rapoport's Rule: the geographic range and genome size of bacterial taxa decline at warmer latitudes - Gavin Lear; Kelvin Lau; Anne‐Marie Perchec; Hannah L. Buckley; Bradley S. Case; Martin Neale; Noah Fierer; Jonathan W. Leff; Kim M. Handley; Gillian Lewis (Environmental Microbiology, 2017)
Summary We sought to test whether stream bacterial communities conform to Rapoport's Rule, a pattern commonly observed for plants and animals whereby taxa exhibit decreased latitudinal range sizes closer to the equator. Using a DNA sequencing approach, we explored the biogeography of biofilm bacterial communities in 204 streams across a ∼1000 km latitudinal gradient. The range sizes of bacterial taxa were strongly correlated with latitude, decreasing closer to the equator, which coincided with a greater than fivefold increase in bacterial taxonomic richness. The relative richness and range size of bacteria were associated with spatially correlated variation in temperature and rainfall. These patterns were observed despite enormous variability in catchment environmental characteristics. Similar results were obtained when restricting the same analyses to native forest catchments, thereby controlling for spatial biases in land use. We analysed genomic data from ∼500 taxa detected in this study, for which data were available and found that bacterial communities at cooler latitudes also tended to possess greater potential metabolic potential. Collectively, these data provide the first evidence of latitudinal variation in the range size distributions of freshwater bacteria, a trend which may be determined, in part, by a trade‐off between bacterial genome size and local variation in climatic conditions.

Jack of all prey, master of some: Influence of habitat on the feeding ecology of a diving marine predator - Jonathan M. Handley; Maëlle Connan; Alastair M. M. Baylis; Paul Brickle; Pierre Pistorius (Marine Biology, 2017)

A novel foraging strategy in gentoo penguins breeding at sub-Antarctic Marion Island - Tegan Carpenter-Kling; Jonathan M. Handley; David B. Green; Ryan R. Reisinger; Azwainewi B. Makhado; Robert J. M. Crawford; Pierre A. Pistorius (Marine Biology, 2017)

Erratum to: Golli Myelin Basic Proteins Modulate Voltage-Operated Ca++ Influx and Development in Cortical and Hippocampal Neurons - V. T. Cheli; D. A. Santiago González; V. Spreuer; V. Handley; A. T. Campagnoni; P. M. Paez (Molecular Neurobiology, 2017)

Analytical models integrated with satellite images for optimized pest management - L. Zack Bright; Michael Handley; Isabel Chien; Sebastian Curi; L. Anders Brownworth; Sebastian D’hers; Ulrich R. Bernier; Pablo Gurman; Noel M. Elman (Precision Agriculture, 2016)

Evaluation and assessment of the efficacy of an abatement strategy in a former lead smelter community, Boolaroo, Australia - P. J. Harvey; M. P. Taylor; L. J. Kristensen; S. Grant-Vest; M. Rouillon; L. Wu; H. K. Handley (Environmental Geochemistry and Health, 2016)

The harlequin ladybird, Harmonia axyridis: global perspectives on invasion history and ecology - Helen E. Roy; Peter M. J. Brown; Tim Adriaens; Nick Berkvens; Isabel Borges; Susana Clusella-Trullas; Richard F. Comont; Patrick De Clercq; Rene Eschen; Arnaud Estoup; Edward W. Evans; Benoit Facon; et al. (Biological Invasions, 2016)

Kleptoparasitism in foraging gentoo penguins Pygoscelis papua - Jonathan M. Handley; Pierre Pistorius (Polar Biology, 2016)

Temporal variation in the diet of gentoo penguins at the Falkland Islands - Jonathan M. Handley; Alastair M. M. Baylis; Paul Brickle; Pierre Pistorius (Polar Biology, 2016)

Identification of the sources of metal (lead) contamination in drinking waters in north-eastern Tasmania using lead isotopic compositions. - P. J. Harvey; H. K. Handley; M. P. Taylor (Environmental Science and Pollution Research, 2015)

Widespread Environmental Contamination Hazards in Agricultural Soils from the Use of Lead Joints in Above Ground Large-Scale Water Supply Pipelines - P. J. Harvey; M. P. Taylor; H. K. Handley (Water, Air, & Soil Pollution, 2015)

Disturbed subsurface microbial communities follow equivalent trajectories despite different structural starting points - Kim M. Handley; Kelly C. Wrighton; Christopher S. Miller; Michael J. Wilkins; Rose S. Kantor; Brian C. Thomas; Kenneth H. Williams; Jack A. Gilbert; Philip E. Long; Jillian F. Banfield (Environmental Microbiology, 2015)
Summary Microbial community structure, and niche and neutral processes can all influence response to disturbance. Here, we provide experimental evidence for niche versus neutral and founding community effects during a bioremediation‐related organic carbon disturbance. Subsurface sediment, partitioned into 22 flow‐through columns, was stimulated in situ by the addition of acetate as a carbon and electron donor source. This drove the system into a new transient biogeochemical state characterized by iron reduction and enriched D esulfuromonadales , C omamonadaceae and B acteroidetes lineages. After approximately 1 month conditions favoured sulfate reduction, and were accompanied by a substantial increase in the relative abundance of D esulfobulbus , D esulfosporosinus , D esulfitobacterium and D esulfotomaculum . Two subsets of four to five columns each were switched from acetate to lactate amendment during either iron (earlier) or sulfate (later) reduction. Hence, subsets had significantly different founding communities. All lactate treatments exhibited lower relative abundances of D esulfotomaculum and B acteroidetes , enrichments of C lostridiales and P sychrosinus species, and a temporal succession from highly abundant C lostridium sensu stricto to P sychrosinus . Regardless of starting point, lactate‐switch communities followed comparable structural trajectories, whereby convergence was evident 9 to 16 days after each switch, and significant after 29 to 34 days of lactate addition. Results imply that neither the founding community nor neutral processes influenced succession following perturbation.

The complete genome sequence for putative H 2 ‐ and S ‐oxidizer C andidatus Sulfuricurvum sp., assembled de novo from an aquifer‐derived metagenome - Kim M. Handley; Daniela Bartels; Edward J. O'Loughlin; Kenneth H. Williams; William L. Trimble; Kelly Skinner; Jack A. Gilbert; Narayan Desai; Elizabeth M. Glass; Tobias Paczian; Andreas Wilke; Dionysios Antonopoulos; et al. (Environmental Microbiology, 2014)
Summary We reconstructed the complete 2.4 Mb‐long genome of a previously uncultivated epsilonproteobacterium, C andidatus Sulfuricurvum sp. RIFRC ‐1, via assembly of short‐read shotgun metagenomic data using a complexity reduction approach. Genome‐based comparisons indicate the bacterium is a novel species within the S ulfuricurvum genus, which contains one cultivated representative, S . kujiense . Divergence between the species appears due in part to extensive genomic rearrangements, gene loss and chromosomal versus plasmid encoding of certain (respiratory) genes by RIFRC ‐1. Deoxyribonucleic acid for the genome was obtained from terrestrial aquifer sediment, in which RIFRC ‐1 comprised ∼ 47% of the bacterial community. Genomic evidence suggests RIFRC ‐1 is a chemolithoautotrophic diazotroph capable of deriving energy for growth by microaerobic or nitrate‐/nitric oxide‐dependent oxidation of S 0 , sulfide or sulfite or H 2 oxidation. Carbon may be fixed via the reductive tricarboxylic acid cycle. Consistent with these physiological attributes, the local aquifer was microoxic with small concentrations of available nitrate, small but elevated concentrations of reduced sulfur and NH 4 + / NH 3 ‐limited. Additionally, various mechanisms for heavy metal and metalloid tolerance and virulence point to a lifestyle well‐adapted for metal(loid)‐rich environments and a shared evolutionary past with pathogenic E psilonproteobacteria . Results expand upon recent findings highlighting the potential importance of sulfur and hydrogen metabolism in the terrestrial subsurface.

Kinetics of urease mediated calcite precipitation and permeability reduction of porous media evidenced by magnetic resonance imaging - S. Handley-Sidhu; E. Sham; M. O. Cuthbert; S. Nougarol; M. Mantle; M. L. Johns; L. E. Macaskie; J. C. Renshaw (International Journal of Environmental Science and Technology, 2013)

The global spread of Harmonia axyridis (Coleoptera: Coccinellidae): distribution, dispersal and routes of invasion - Peter M. J. Brown; Cathleen E. Thomas; Eric Lombaert; Daniel L. Jeffries; Arnaud Estoup; Lori-Jayne Lawson Handley (BioControl, 2011)

Ecological genetics of invasive alien species - L.-J. Lawson Handley; A. Estoup; D. M. Evans; C. E. Thomas; E. Lombaert; B. Facon; A. Aebi; H. E. Roy (BioControl, 2011)

Comparative susceptibility of Salmonella Typhimurium biofilms of different ages to disinfectants - Hui San Wong; Kirsty M. Townsend; Stan G. Fenwick; Garth Maker; Robert D. Trengove; Ryan M. O'Handley (Biofouling, 2010)

Redox cycling of arsenic by the hydrothermal marine bacterium Marinobacter santoriniensis - Kim M. Handley; Marina Héry; Jonathan R. Lloyd (Environmental Microbiology, 2009)
Summary Marinobacter santoriniensis NKSG1 T is a mesophilic, dissimilatory arsenate‐reducing and arsenite‐oxidizing bacterium isolated from an arsenate‐reducing enrichment culture. The inoculum was obtained from arsenic‐rich shallow marine hydrothermal sediment from Santorini, Greece, with evidence of arsenic redox cycling. Growth studies demonstrated M. santoriniensis NKSG1 T is capable of conserving energy from the reduction of arsenate [As(V)] with acetate or lactate as the electron donor, and of oxidizing arsenite [As(III)] heterotrophically with oxygen as the electron acceptor. The oxidation of As(III) coincided with the expression of the aoxB gene encoding for the catalytic molybdopterin subunit of the heterodimeric arsenite oxidase operon, indicating the reaction is enzymatically controlled, and M. santoriniensis NKSG1 T is a heterotrophic As(III)‐oxidizing bacterium. Although it is clear that this organism also performs dissimilatory As(V) reduction, no amplification of the arrA arsenate reductase gene was attained using a range of primers and PCR conditions. Marinobacter santoriniensis NKSG1 T belongs to a genus of bacteria widely occurring in marine environments, including hydrothermal sediments, and is among the first marine bacteria shown to be capable of either anaerobic As(V) respiration or aerobic As(III) oxidation.

Drought‐induced nitrous oxide flux dynamics in an enclosed tropical forest - Joost L. M. Van Haren; Linda L. Handley; Karl Y. Biel; Valery N. Kudeyarov; Jean E. T. McLain; Dean A. Martens; Debra C. Colodner (Global Change Biology, 2005)
El Niño–La Niña cycles strongly influence dry and wet seasons in the tropics and consequently nitrous oxide (N 2 O) emissions from tropical rainforest soils. We monitored whole‐system and soil chamber N 2 O fluxes during 5‐month‐long droughts in the Biosphere 2 tropical forest to determine how rainfall changes N 2 O production. A consistent pattern of N 2 O flux changes during drought and subsequent wetting emerged from our experiments. Soil surface drying during the first days of drought, presumably increased gas transport out of the soil, which increased N 2 O fluxes. Subsequent drying caused an exponential decrease in whole‐system (4.0±0.1% day −1 ) and soil chamber N 2 O flux (8.9±0.8% day −1 ; south chamber; and 13.7±1.1% day −1 ; north chamber), which was highly correlated with soil moisture content. Soil air N 2 O concentration ([N 2 O]) and flux measurements revealed that surface N 2 O production persisted during drought. The first rainfall after drought triggered a N 2 O pulse, which amounted to 25% of drought‐associated reduction in N 2 O flux and 1.3±0.4% of annual N 2 O emissions. Physical displacement of soil air by water and soil chemistry changes during drought could not account for the observed N 2 O pulse. We contend that osmotic stress on the microbial biomass must have supplied the N source for pulse N 2 O, which was produced at the litter–soil interface. After the pulse, N 2 O fluxes were consistently 90% of predrought values. Nitrate change rate, nutrient, [N 2 O], and flux analyses suggested that nitrifiers dominated N 2 O production during the pulse and denitrifiers during wet conditions. N 2 O flux measurements in Biosphere 2, especially during the N 2 O pulse, demonstrate that large‐scale integration methods, such as flux towers, are essential for improving ecosystem N 2 O flux estimates.

Increased leaf area dominates carbon flux response to elevated CO 2 in stands of Populus deltoides (Bartr.) - Ramesh Murthy; Greg Barron‐Gafford; Phillip M. Dougherty; Victor C. Engel; Katie Grieve; Linda Handley; Christie Klimas; Mark J. Potosnak; Stanley J. Zarnoch; Jianwei Zhang (Global Change Biology, 2005)
We examined the effects of atmospheric vapor pressure deficit (VPD) and soil moisture stress (SMS) on leaf‐ and stand‐level CO 2 exchange in model 3‐year‐old coppiced cottonwood ( Populus deltoides Bartr.) plantations using the large‐scale, controlled environments of the Biosphere 2 Laboratory. A short‐term experiment was imposed on top of continuing, long‐term CO 2 treatments (43 and 120 Pa), at the end of the growing season. For the experiment, the plantations were exposed for 6–14 days to low and high VPD (0.6 and 2.5 kPa) at low and high volumetric soil moisture contents (25–39%). When system gross CO 2 assimilation was corrected for leaf area, system net CO 2 exchange (SNCE), integrated daily SNCE, and system respiration increased in response to elevated CO 2 . The increases were mainly as a result of the larger leaf area developed during growth at high CO 2 , before the short‐term experiment; the observed decline in responses to SMS and high VPD treatments was partly because of leaf area reduction. Elevated CO 2 ameliorated the gas exchange consequences of water stress at the stand level, in all treatments. The initial slope of light response curves of stand photosynthesis (efficiency of light use by the stand) increased in response to elevated CO 2 under all treatments. Leaf‐level net CO 2 assimilation rate and apparent quantum efficiency were consistently higher, and stomatal conductance and transpiration were significantly lower, under high CO 2 in all soil moisture and VPD combinations (except for conductance and transpiration in high soil moisture, low VPD). Comparisons of leaf‐ and stand‐level gross CO 2 exchange indicated that the limitation of assimilation because of canopy light environment (in well‐irrigated stands; ratio of leaf : stand=3.2–3.5) switched to a predominantly individual leaf limitation (because of stomatal closure) in response to water stress (leaf : stand=0.8–1.3). These observations enabled a good prediction of whole stand assimilation from leaf‐level data under water‐stressed conditions; the predictive ability was less under well‐watered conditions. The data also demonstrated the need for a better understanding of the relationship between leaf water potential, leaf abscission, and stand LAI.

What fraction of the organic carbon in sacoglossans is obtained from photosynthesis by kleptoplastids? An investigation using the natural abundance of stable carbon isotopes - J. A. Raven; D. I. Walker; K. R. Jensen; L. L. Handley; C. M. Scrimgeour; S. G. McInroy (Marine Biology, 2001)

Genetic population structure and introgression in Anopheles dirus mosquitoes in South‐east Asia - Catherine Walton; Jane M. Handley; Frank H. Collins; Visut Baimai; Ralph E. Harbach; Vanida Deesin; Roger K. Butlin (Molecular Ecology, 2001)
Genetic structure and species relationships were studied in three closely related mosquito species, Anopheles dirus A, C and D in Thailand using 11 microsatellite loci and compared with previous mitochondrial DNA (mtDNA) data on the same populations. All three species were well differentiated from each other at the microsatellite loci. Given the almost complete absence of mtDNA differentiation between An. dirus A and D, this endorses the previous suggestion of mtDNA introgression between these species. The high degree of differentiation between the northern and southern population of An. dirus C ( R ST = 0.401), in agreement with mtDNA data, is suggestive of incipient species. The lack of genetic structure indicated by microsatellites in four populations of An. dirus A across northern Thailand also concurs with mtDNA data. However, in An. dirus D a limited but significant level of structure was detected by microsatellites over ~400 km in northern Thailand, whereas the mtDNA detected no population differentiation over a much larger area (>1200 km). There is prior evidence for population expansion in the mtDNA. If this is due to a selective sweep originating in An. dirus D, the microsatellite data may indicate greater barriers to gene flow within An. dirus D than in species A. Alternatively, there may have been historical introgression of mtDNA and subsequent demographic expansion which occurred first in An. dirus D so enabling it to accumulate some population differentiation. In the latter case the lack of migration‐drift equilibrium precludes the inference of absolute or relative values of gene flow in An. dirus A and D.

Effects of nicotine on head-shakes and tryptophan metabolites - Colin M. Gaynor; Sheila L. Handley (Psychopharmacology, 2001)

The isolation and characterization of microsatellites from Anopheles dirus mosquitoes - C. Walton; M. S. Chang; J. M. Handley; R. E. Harbach; F. H. Collins; V. Baimai; R. K. Butlin (Molecular Ecology, 2000)

Anisotropy of Young's modulus of human tibial cortical bone - B. K. Hoffmeister; S. R. Smith; S. M. Handley; J. Y. Rho (Medical & Biological Engineering & Computing, 2000)

Nitrogen and Sulfur Input-Output Budgets in the Experimental and Reference Watersheds, Bear Brook Watershed in Maine (BBWM) - J. Kahl; S. Norton; I. Fernandez; L. Rustad; M. Handley (Environmental Monitoring and Assessment, 1999)

Sequence diversity in the coat protein coding region of twelve sugarcane mosaic potyvirus isolates from Australia, USA and South Africa - J. A. Handley; G. R. Smith; J. L. Dale; R. M. Harding (Archives of Virology, 1998)

A theory for 15 N/ 14 N fractionation in nitrate-grown vascular plants - David Robinson; L. L. Handley; C. M. Scrimgeour (Planta, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Shoot ?15N correlates with genotype and salt stress in barley - L. L. Handley; D. Robinson; B. P. Forster; R. P. Ellis; C. M. Scrimgeour; D. C. Gordon; E. Nevo; J. A. Raven (Planta, 1997)

Comparison of shoot dry weight, Na+ content and δ13C values of ari-e and other semi-dwarf barley mutants under salt-stress - H. Pakniyat; L.L. Handley; W.T.B. Thomas; T. Connolly; M. Macaulay; P.D.S. Caligari; B.P. Forster (Euphytica, 1997)

Sequence diversity in the NIb coding region of eight sugarcane mosaic potyvirus isolates infecting sugarcane in Australia - J. A. Handley; G. R. Smith; J. L. Dale; R. M. Harding (Archives of Virology, 1996)